From social to intangible remittances: Toward a comprehensive framework of remittances - Janine Isabelle Pinkow-Läpple; Judith Möllers (Comparative Migration Studies, 2025)
Levitt's ground-breaking concept of social remittances has inspired many empirical studies in migration research, yet its theoretical underpinnings remain relatively underdeveloped. Most fundamentally, the interpretations of what social remittances are have multiplied, posing the risk of reducing the term to little more than a catchphrase. To address this issue, this paper undertakes a systematic review of various conceptualisations of social remittances. We identify four primary areas of divergence within the existing literature on social remittances: the scope of the concept, i.e. the delineation of its boundaries, the underlying process of how social remittances are acquired and transferred, the spatial dimension of these transfers, particularly their direction, and the classification of subtypes of social remittances. Taking this as our starting point, we propose advancing Levitt's original concept towards what we will term intangible remittances. Our advanced concept accounts for the multidimensionality of intangible remittances and provides essential clarifications in terms of delineation and terminology. Additionally, we put forward a fine-grained typology of different subtypes of intangible remittances, categorising them based on their content (that might be economic, environmental, political, or socio-cultural) and form (knowledge, normative structures, or practices). In summary, we provide a comprehensive framework of intangible remittances that not only integrates other emerging concepts, such as political remittances but also seamlessly aligns with the broader superordinate concept of remittances.
Keywords: 330; intangible remittances; social remittances; theory; conceptual framework; typology; migration